Role of Self Help Groups in Women Development- an Empirical Study - Amutha, D. (International Journal of Bio-resource and Stress Management, 2011)
SHGs enhance the equality of status of women as participants, decision-makers and beneficiaries in the democratic, economic, social and cultural spheres of life. The basic principles of the SHGs are group approach, mutual trust, organization of small and manageable groups, group cohesiveness, sprit of thrift, demand based lending, collateral free, women friendly loan, peer group pressure in repayment, skill training, capacity building and empowerment. This study aims at evaluating the development of rural women through SHGs and availing microfinance in two blocks from Tuticorin District, Tamilnadu state, India viz, Pudur and Kayathar. This study is compiled with the help of the primary data covered only three months period (2011). Totally 216 respondents were selected from 12 SHGs of two blocks by using simple random sampling method. This is purely a descriptive study. Percentage, average, χ² tests, t tests, correlation, Cramer’s V, standard deviation (δ), variance (δ²) and probability analysis were used. The positive changes have been reported in case of awareness regarding nutrition, health, hygiene, family planning, decision making related to money centered, interaction with outsiders, mobility, educational development, access to health services, family income etc. The result of χ² analysis revealed that there is significant relationship between socio-economic status after joining SHGs and SHGs members in two blocks from Tuticorin District study area.